Pembinaan Akhlak Peserta Didik Melalui Ekstrakurikuler Kerohanian Islam Di SMA Negeri 10 Gowa - Aladin Mohd. Wardyan Al-Mukhtasin; Muzakkir Muzakkir; Andi Achruh (LPPM IAIN Sorong, 2024)
This study aims to describe the planning, implementation, and evaluation of moral development of students through extracurricular Islamic spirituality at SMA Negeri 10 Gowa. This type of research is qualitative with a case study model. Data collection in this research uses observation, interview, and documentation methods. Next, the data is collected, reduced, presented, and then inferred. At the end triangulation is carried out. The results of this study show that: 1) Planning: not made in a structured or systematic manner, but activities just run and run continuously. 2) Implementation: reading the Qur'an for 10-15 minutes, congregational zuhur prayer, Friday study (KAMAT), clean Friday, literacy, recitation, memorization of juz 30, Isra Mikraj celebration, pesantren kilat, and iftar together. 3) Evaluation: looks at the morals of students in terms of religion, social spirit, and concern for the environment. The supporting factors are support from parents, teacher support, and support from the school. While the inhibiting factors are the lack of awareness of students to follow activities, and excessive use of social media.